Investigation of Protein Corona Formed around Biologically Produced Gold Nanoparticles - Pourali, Parastoo; Neuhöferová, Eva; Dzmitruk, Volha; Benson, Veronika (Materials (Basel, Switzerland), 2022)
Although there are several research articles on the detection and characterization of protein corona on the surface of various nanoparticles, there are no detailed studies on the formation, detection, and characterization of protein corona on the surface of biologically produced gold nanoparticles (AuNPs). AuNPs were prepared from Fusarium oxysporum at two different temperatures and characterized by spectrophotometry, Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), and energy-dispersive X-ray spectroscopy (EDS). The zeta potential of AuNPs was determined using a Zetasizer. AuNPs were incubated with 3 different concentrations of mouse plasma, and the hard protein corona was detected first by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and then by electrospray liquid chromatography-mass spectrometry (LC-MS). The profiles were compared to AuNPs alone that served as control. The results showed that round and oval AuNPs with sizes below 50 nm were produced at both temperatures. The AuNPs were stable after the formation of the protein corona and had sizes larger than 86 nm, and their zeta potential remained negative. We found that capping agents in the control samples contained small peptides/amino acids but almost no protein(s). After hard protein corona formation, we identified plasma proteins present on the surface of AuNPs. The identified plasma proteins may contribute to the AuNPs being shielded from phagocytizing immune cells, which makes the AuNPs a promising candidate for in vivo drug delivery. The protein corona on the surface of biologically produced AuNPs differed depending on the capping agents of the individual AuNP samples and the plasma concentration.
Keywords: biologically produced gold nanoparticles; capping agent; hard protein corona; Fusarium oxysporum